Diagnostic and treatment delay among Tuberculosis patients in Afar Region, Ethiopia: A cross-sectional study - Belay Mulugeta; Bjune Gunnar; Ameni Gobena; Abebe Fekadu (BMC, 2012)
Abstract Background TB is a major public health problem globally and Ethiopia is 8th among the 22 high burden countries. Early detection and effective treatment are pre-requisites for a successful TB control programme. In this regard, early health seeking action from patients' side and prompt diagnosis as well as initiation of treatment from the health system's side are essential steps. The aim of this study was to assess delay in the diagnosis and treatment of TB in a predominantly pastoralist area in Ethiopia. Methods On a cross-sectional study, two hundred sixteen TB patients who visited DOTS clinics of two health facilities in Afar Region were included consecutively. Time from onset of symptoms till first consultation of formal health providers (patients' delay) and time from first consultation till initiation of treatment (health system's delay) were analyzed. Results The median patients' and health system's delay were 20 and 33.5 days, respectively. The median total delay was 70.5 days with a median treatment delay of 1 day. On multivariate logistic regression, self-treatment (aOR. 3.99, CI 1.50-10.59) and first visit to non-formal health providers (aOR. 6.18, CI 1.84-20.76) were observed to be independent predictors of patients' delay. On the other hand, having extra-pulmonary TB (aOR. 2.08, CI 1.08- 4.04), and a first visit to health posts/clinics (aOR. 19.70, CI 6.18-62.79), health centres (aOR. 4.83, CI 2.23-10.43) and private health facilities (aOR. 2.49, CI 1.07-5.84) were found to be independent predictors of health system's delay. Conclusions There is a long delay in the diagnosis and initiation of treatment and this was mainly attributable to the health system. Health system strengthening towards improved diagnosis of TB could reduce the long health system's delay in the management of TB in the study area.